Diversity of potamodromous fishes in the Tocantins-Araguaia basin - Thiago Nascimento da Silva Campos; Hasley Rodrigo Pereira; Phâmela Bernardes Perônico; Carine Cavalcante Chamon; Philip Teles Soares; Fernando Mayer Pelicice (Neotropical Ichthyology)
Abstract Migratory fishes are deeply connected with human societies. In the Tocantins-Araguaia basin, a region marked by high biodiversity, endemism and environmental degradation, there is little information about these fishes. In this scenario, the present study investigated taxonomic and functional diversity of potamodromous fishes, with the objective to compile the first species list, and examine patterns in species richness, composition, and functional diversity. The migratory status of each species was assigned based on the most recent literature on fish diversity in the Tocantins-Araguaia and Amazon basins. The study consolidated a list of 77 potamodromous fish species (three orders, 12 families and 41 genera), including eight endemic, three threatened and two non-native species. Pimelodidae summed most species, followed by Serrasalmidae and Curimatidae. Most species were classified as medium (42) and long-distance (32) migrants, with few carrying out continental migrations (3). Most species were widely distributed in the basin, resulting in little spatial variation in species richness, composition and functional diversity. However, trait composition varied among species, families and migratory scale. This is the first broad assessment focused on migratory fishes in this basin, with potential to generate basic information to support fisheries management, environmental planning, and conservation initiatives.